Predicting success of mobile game after market launch using app downloads and sales revenues as performance indicators - Kyungjin Nam; Hyejin Kim (International Telecommunications Society (ITS), 2018)
The world game industry, especially the mobile game market, has grown rapidly in recent years. One of the interesting characteristics of mobile game performance is that its lifetime is remarkably short compared to that of online games and most downloads are peaked in the early period of the service. Since the success of the game is largely dependent of this early performance, this study aims to predict the performance of mobile games right after launch and identify the factors which have influences on the success of the game. Using a multiple regression analysis with mobile game application downloads and sales revenue as performance indicators, this paper investigates the impacts of five main categories of independent variables; brand-related (awareness of IP and name value of publishers), information sources (platform rating and official domestic forum), media and promotion factors (TV commercials, pre-registration, press releases, YouTube videos), objective features (genre and payment type), and distribution-related variables (platform's market power and seasonal issues). TV commercial and pre-registration are significantly strong factors for both revenue and downloads. Google Play's featured banner and media and promotion factors such as press releases and YouTube videos are also important in revenue increase. Regarding the number of downloads, the use of IP (intellectual property) is a significant factor and puzzle games have relatively positive relationship than other genres. Surprisingly, however, the publishing firm (or rather the name value of the firm) didn't have significant impact on performance, and this might imply that there could be an opportunity for small and medium sized companies by investing in media and obtaining mobile platform advantages.
Keywords: 330; Mobile game industry; Game revenue; Game downloads; Regression analysis